Reconstitution of Dastur and Co. - Planning Commission (Planning Commission Government of India, 1965)
The analysis on the reconstitution of Dastur & Company (Dasturco) evaluates the strategic transformation of the established consulting engineering firm to enhance India’s self-reliance in industrial consultancy, particularly within the steel sector. Motivated by government policies and industrialization goals, the report examines Dasturco’s competence, project scope, financial viability, and organizational framework. Findings highlight the firm’s proven track record in complex projects, including Bokaro steel plant engagements, and project sustained demand for its services. Recommendations propose partial government ownership with 20–50% equity, retention of existing technical leadership, and employee participation through shareholding to maintain operational efficiency while ensuring accountability. The report cautions against bureaucratic inefficiencies and emphasizes a balanced approach that preserves professional autonomy, incentivizes performance, and secures quality consultancy services. Overall, the reconstitution strategy aims to strengthen Dasturco’s role in India’s industrial development, fostering advanced engineering capabilities aligned with national growth objectives.
Government of India Planning Commission
Keywords: Dastur & Company; Reconstitution; Public Sector Undertaking; Engineering Consultancy; Steel Industry; Industrial Development; Operational Autonomy; Financial Viability; Management Structure; Employee Participation; Government Oversight; Project Planning